Which Trauma Patients Require Lower Enoxaparin Dosing for Venous Thromboembolism Prophylaxis?. Issue 10 (6th November 2020) - Veatch, Jessica; Hashim, Yassar; Dhillon, Navpreet K.; Toscano, Samantha; Mason, Russell; Lin, Ting-Lung; Barmparas, Galinos; Ley, Eric J.
Trauma patients have a high risk for venous thromboembolism (VTE) such that an increased enoxaparin dose is necessary to reduce related complications. Given that most trauma patients require an enoxaparin dose of at least 40 mg every 12 hours for VTE prophylaxis, we sought to identify which patients require enoxaparin 30 mg every 12 hours and hypothesized that both weight and low creatinine clearance (CrCl) would more likely determine enoxaparin dosing than age, body mass index (BMI), or body surface area (BSA). Single institution data were collected on trauma patients between August 2014 and February 2018 to compare trauma patients who required enoxaparin 30 mg to those who required ≥40 mg every 12 hours. Of the 245 patients included, 86 (35.1%) required enoxaparin at 30 mg to achieve the goal anti-factor Xa trough level. Factors associated with low dose enoxaparin were older age (59.6 vs. 46.2 years, P ≤ .01) and lower CrCl (81.5 mL/min vs. 93.7 mL/min, P ≤ .01). Weight, BSA, and BMI did not alter the dose of enoxaparin. A regression model determined that only CrCl predicted the need for low dose enoxaparin (adjusted odds ratio .982, 95% CI: .975-.990, P < .01). Although an initial dose of enoxaparin 40 mg is appropriate for most trauma patients, patients with low CrCl should receive 30 mg. Increased age and low weight were not associated with the need for a lower enoxaparin dose.